Scanning of antennae and maxillary palps of anthropophilic Aedes aegypti and ornithophilic Culex pipiens as potential arbovirus vectors - Faten Abouelmagd; Mohamed Elmutasim Elsheikh; Elshiekh Khidir; Mohammed Radwan; Karim Mohamed Rashad; Manal El Said (Veterinary World, 2024)
Background and Aim: Efficient mosquito vectors are required to persist and propagate arthropod-borne diseases that seriously affect impoverished populations worldwide. Mosquito sensilla plays a crucial role in host-seeking and disease transmission to humans. This study aimed to distinguish between the several types of sensilla found on the antennae and maxillary palps of Culex pipiens and Aedes aegypti, matching this diversity with host preference and disease transmission.